Understanding chemically processed solar cells based on quantum dots - Victor Malgras; Andrew Nattestad; Jung Ho Kim; Shi Xue Dou; Yusuke Yamauchi (Science and Technology of Advanced Materials, 2017)
Photovoltaic energy conversion is one of the best alternatives to fossil fuel combustion. Petroleum resources are now close to depletion and their combustion is known to be responsible for the release of a considerable amount of greenhouse gases and carcinogenic airborne particles. Novel third-generation solar cells include a vast range of device designs and materials aiming to overcome the factors limiting the current technologies. Among them, quantum dot-based devices showed promising potential both as sensitizers and as colloidal nanoparticle films. A good example is the p-type PbS colloidal quantum dots (CQDs) forming a heterojunction with a n-type wide-band-gap semiconductor such as TiO2 or ZnO. The confinement in these nanostructures is also expected to result in marginal mechanisms, such as the collection of hot carriers and generation of multiple excitons, which would increase the theoretical conversion efficiency limit. Ultimately, this technology could also lead to the assembly of a tandem-type cell with CQD films absorbing in different regions of the solar spectrum.